DNA methylation of ACADS promotes immunogenic cell death in hepatocellular carcinoma - Ze Qian; Yifan Jiang; Yacong Wang; Yu Li; Lin Zhang; Xiaofeng Xu; Diyu Chen (Cell & Bioscience)
Abstract Background Altered metabolism has become an important characteristic of cancer, and acyl-CoA dehydrogenase short-chain (ACADS), a regulator of lipid synthesis, is involved in carcinogenesis-associated metabolic pathways. DNA methylation is an important mechanism for silencing ACADS in various malignancies. However, the specific role of ACADS in hepatocellular carcinoma (HCC) pathogenesis remains poorly understood. Methods and results Using RNA sequencing data from different tumours in The Cancer Genome Atlas database, we observed that ACADS was downregulated and hypermethylated in HCC. Three potential CpG island sites (cg01535453, cg08618068, and cg10174836) were identified in the ACADS promoter. Through in vivo and in vitro experiments, we confirmed that cg08618068 was methylated in HCC. We defined this site as ACADS methylation site-2 (ACADS MS-2). Methylation of ACADS MS-2 was associated with worse survival, and mutation of MS-2 increased ACADS mRNA levels in five HCC cell lines. Sustained overexpression of ACADS not only suppressed the proliferation, migration, and invasion of HCC cells but also promoted immunogenic cell death (ICD) via the upregulation of calreticulin. Subsequently, we established a specific nomogram based on ACADS methylation levels to evaluate the 3- and 5-year overall survival rates of patients with HCC who underwent surgical resection. Conclusions Our work clarified that ACADS acts as a putative tumour suppressor in HCC and confirmed that a nomogram including ACADS methylation had good predictive performance in HCC. We also discovered a correlation between ACADS and ICD, suggesting that ACADS is an essential target for immunotherapy in HCC. Graphical Abstract